MODULAR PHOTOVOLTAIC ROOFING SYSTEM, METHOD FOR INSTALLING THEREOF AND SOLAR ROOF - LACH Mariusz (2024)
The subject-matter of the present invention is a modular photovoltaic roofing system comprising: plurality of modular roof panels (40) integrated with photovoltaic modules (50); an at least one longitudinal channel profile (20) for routing electrical cables (K); an at least one longitudinal side profile (30) for mounting electric or electronic devices. The subject-matter of the invention is also a solar roof equipped with the modular photovoltaic roofing system and a method of its installation. El objeto de la presente invención es un sistema modular de cubierta fotovoltaica que comprende: pluralidad de paneles de cubierta modulares (40) integrados con módulos fotovoltaicos (50); un perfil de canal longitudinal (20) para el tendido de cables eléctricos (K); un perfil lateral longitudinal (30) para el montaje de dispositivos eléctricos o electrónicos. El objeto de la invención es también una cubierta solar equipada con el sistema modular de cubierta fotovoltaica y un método de su instalación.